2022
DOI: 10.1002/adfm.202113191
|View full text |Cite
|
Sign up to set email alerts
|

Boron‐Tethering and Regulative Electronic States Around Iridium Species for Hydrogen Evolution

Abstract: The performance of single-atom electrocatalysts usually suffers from attenuation due to high energy states, especially in harsh environments. Therefore, as high-efficiency electrocatalysts for hydrogen reduction reaction (HER), supported metal nanoclusters (NCs) with maximum metal atom efficiency are promising, yet the genuine mechanism involving rational orbital modulation is still arguable. Herein, the conjugating effect between electron-donor boron (B)-tethering engineering and iridium (Ir) that facilitates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…And the contribution of nickel foam to the performance is negligible. The Tafel slope was achieved by combining the LSV curve with the Tafel equation as follows: 38,39 η = a + b log j where η is the overpotential, a is a constant value, b is the Tafel slope, and j is the current density. The kinetics of electron transfer on the catalyst surface during the HER was studied using the Tafel slope.…”
Section: Resultsmentioning
confidence: 99%
“…And the contribution of nickel foam to the performance is negligible. The Tafel slope was achieved by combining the LSV curve with the Tafel equation as follows: 38,39 η = a + b log j where η is the overpotential, a is a constant value, b is the Tafel slope, and j is the current density. The kinetics of electron transfer on the catalyst surface during the HER was studied using the Tafel slope.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon materials have a large specific surface area, low cost, and good electrical conductivity, so they are widely used as substrate materials. [200,201] For example, N-doped graphene sheets can achieve effective anchoring of Ir nanoparticles on their surfaces. [202] The theoretical calculation results showed that the introduction of N F I G U R E 14 Strategies to improving the stability of catalysts effectively reduced the adhesion energy of the graphene substrate to the Ir clusters.…”
Section: Electronic Coupling Routementioning
confidence: 99%
“…In this section, the relationship between the evolution of the coordination environment surrounding the active metal sites and the HER performance will be further discussed. 65,84,[87][88][89][90][91] Aiming to convincingly design prominent SACs for the HER, a range of rational strategies to construct active centers and adjust the coordination configuration has been proposed, which includes tuning doping heteroatoms, 92,93 organic ligands, 94 optimizing mass loading 95,96 and defect engineering, 97 etc. In consideration of the electrocatalytic activity and cost, SACs towards the HER can be divided into precious metal active centers (Pt, Ru, Ir, Rh, etc.)…”
Section: Advances In Sacs For Hydrogen Generationmentioning
confidence: 99%